PENYULUHAN PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT ( PHBS ) DI LINGKUNGAN SEKOLAH PADA ANAK SDN 1 GADUNGSARI KECAMATAN TIRTOYUDO KABUPATEN MALANG - Desi Urbasari; Purwaning Budi Lestari (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2023)
Community service activities regarding counseling on juvenile delinquency for students of SD Negeri 1 Gadungsari, Tirtoyudo District, Malang Regency aim to reduce the risk of disease in school children (aged 6-10 years), create a supportive learning atmosphere because a clean school environment can increase student enthusiasm and learning achievement at school. They can experience negative impacts if they do not carry out PHBS in the school environment, such as diseases that arise due to unhealthy lifestyles, and the impact of an unclean school environment. The method used in this community service activity is direct counseling in collaboration with several agencies, namely the Gadungsari Village Government and Gadungsari 1 Public Elementary School. The material presented in the counseling activities included various PHBS in the school environment, the negative impact of not doing PHBS in the school environment. The output of this counseling activity is that Grade VI students at SD Negeri 1 Gadungsari will be equipped to be able to apply PHBS in the school environment and to respond to the impact of an environment that does not implement PHBS which has a negative impact on those who are unable to choose actions and behaviors that are not good for health. From this provision, it is hoped that they will be able to realize it in themselves so that they can become the next generation of a nation that is healthy, of superior quality.